NOVEL SANG PEMIMPI KARYA ANDREA HIRATA : ANALISIS HABITUS DAN MODAL DALAM ARENA PENDIDIKAN MENURUT PERSPEKTIF PIERRE BOURDIEU - Harpindo Syah Putra Hilarion Ginting (Universitas Sanata Dharma, 2019)
The purposes of this research is describing the habits and capital in Sang Pemimpi novels. Thisresearch paradigm uses M. H. Abrams paradigm with discursive approach. Discursive approach usesPierre Bourdieu theory. Method and data collecting technique which are employed in this research islibrary research. Data analysis method in this research is used content analysis method. Contentanalysis method is used to discover and understand the habits and capital in Sang Pemimpi novel.Theresults of habits and capital analysis in Sang Pemimpi novel are: Ikal has 6 habitus, namely: hardworker, never give up, like to exercise, fight pessimism, save money, and religious. Arai has 6 habits,namely: hard worker, never give up, optimistic, always curious, save money, and generous. Jimbronhas 4 habits, namely: hard worker, obsession with horses, save money, and innocent. Analysis ofcapital includes economic, culture, social, and symbolic. Analysis of economic capital shows that Ikal,Arai, and Jimbron do not have economic capital. Analysis of culture capital shows that Ikal has moredominant cultural capital than Arai and Jimbron. Analysis of social capital shows that Ikal, Arai, andJimbron have social capital. Analysis of symbolic capital shows that Ikal, Arai, and Jimbron do nothave symbolic capital.